Folk, folklore, and folkloristics : interpenetration of society and folklore - Chakrabarti, Bikas (Kolkata : Mitram, 2010)
Contributed research papers; mostly with reference to West Bengal
Includes bibliographical references and index
Keywords: Folklore -- India -- West Bengal; West Bengal (India) -- Social life and customs